Unsur Pembangun dalam Sastra Anak Novel Mata di Tanah Melus Karya Okky Madasari: Kajian Strukturalisme - Nur Cahyati; Heny Friantary; Ixsir Eliya (ESTETIK : Jurnal Bahasa Indonesia, 2021)
Children's literature produced in Indonesia it self is not too much and studies are rarely carried out. Therefore, it is important to have an assessment of children's literature, especially novels. The research objective was to describe the building blocks in Okky Madasari's Mata di Tanah Melus novel. The approach used in this research is a structuralism approach. The research method used content analysis method. The data source is the novel Mata di Tanah Melus by Okky Madasari. The research time was carried out for one month. Data collection techniques using library techniques. The data collection instrument was the novel Mata di Tanah Melus by Okky Madasari. The data validity technique uses credibility testing techniques, namely increasing persistence and using reference materials. Data analysis in this study used Miles and Huberman's analysis model, namely data collection, data reduction, data presentation, and conclusions. The results showed that the building blocks found in the novel Mata di Tanah Melus, namely the facts of the story in the form of a forward plot. The main character is Matara, the supporting character consists of 18 people, the white character consists of 5 people, and the black character is the Hunters. The setting consists of 17 places. The time setting occurs in the morning, noon, and night. The socio-cultural background raises the culture of the Melus Tribe. The theme raised in the novel Mata di Tanah Melus is the theme of humanity. The means of the story are titles and points of view. The title of the novel contains two meanings and experiences semantic distortion. The point of view used is the main actor's first person point of view